MRI of perianal fistulae: a pictorial kaleidoscope. Issue 12 (December 2015) - Kumar, N.; Agarwal, Y.; Chawla, A. Singh; Jain, R.; Thukral, B. Bhushan
Abstract : Perianal fistulae are an abnormal communication between the anorectum and the perianal skin. A seemingly benign condition, it can be a cause of considerable distress to the patient if it is not mapped out adequately before embarking upon surgical correction. The persistence of residual disease complicates and up-stages the grade of the remnant fistula with increased risk of anal incontinence following surgery secondary to damage to the anal sphincter complex. Magnetic resonance imaging (MRI) can play a critical role in mapping the fistulae tract in relation to the anal sphincter complex and hence, act as a reliable guide for the surgeon to chart the optimised management of perianal fistulae. This review illustrates the role of MRI in the imaging evaluation of perianal fistulae, to facilitate a well-planned surgical course.